Autonomia feminina no processo de parto e nascimento: um estudo fenomenológico na perspectiva de profissionais - Reis, Thamiza Laureany da Rosa dos Reis (2017)
Childbirth as a physiological event of women`s sexual and reproductive life must be accompanied and assisted in a way that the woman experiences it actively, acting as protagonist during process. The need to deepen researches on women`s autonomy in physiological delivery scenario; it is perceived that need especially from the involved social actors’ perspective. Thus, reflecting about the theme, the guiding research question is: How do professionals who participate in obstetric care provide to women the exercise of their autonomy during labor and delivery? The objectives are: To describe the actions taken for professionals that promote women`s exercise of autonomy; To apprehend the “reasons why” for the actions carried out by health professionals involved in assisting women during labor and delivery; To apprehend the characteristics of actions of professionals who assist women during labor. Qualitative investigation based on the social phenomenology of Alfred Schütz. The study setting was the University Hospital of Santa Maria`s Obstetric Center and the participants were 17 health professionals working in the care for obstetric labor and delivery. Data collection occurred from March to May of 2016 using the phenomenological interview; the collection was closed when there was sufficiency of meanings. The characteristics of actions developed for professionals who assisted women during labor and delivery were analyzed through comprehensive interpretation and phenomenological analysis. Were disclosed the concrete categories of lived experiences for the reasons “for” and “why”. Regarding the “reasons for” emerged the categories: "the best for everyone involved in labor and delivery" and "recognition and expectation of changes in obstetric care". For the “reasons why” emerged: "history of life and the condition of being human" and "professional experience and access to scientific evidence". From the social perspective it was revealed that the actions carried out by professionals assisting during labor are oriented from different situations in lifeworld being influenced by the social group in which they are inserted; by their own experiences and the knowledge derived from the professional qualification. Anchored in their moral and ideological position, professionals sometimes presented a disfigured conception of women`s autonomy in relation to the process of parturition. Based on these results, it is intended to foment the strengthening of an attentive look and a comprehensive attitude towards the autonomous experience of parturition based on the possibility of professionals to rethink their practices and paradigms.